Islamic Character Values through Ratéeb Meuseukat Dance Learning from Al-Muna Teachers Kindergarten Bireuen - Juli Saputra, Rudy; Basri, Novysa; Kharizmi, Muhammad; Halim, Fauziatul; Aryesha, Vinny (Catharsis, 2023)
This research is motivated by the fact that there are still teachers who do not teach the traditional Ratéeb Meuseukat dance at Almuna Bireuen Kindergarten, which should be very good to teach because there is a knowledge transfer process in learning this dance. Such as character values ​​which are very important in cultivating children's Islamic character and love of their own culture in students at Kindergarten Almuna Bireuen. This research aims to foster Islamic character education in teachers which can then be implemented and transmitted to students through instilling Islamic values ​​from the dance taught. Data collection used were observation instruments, interviews and document studies. Data analysis techniques use data reduction, data presentation, and data verification. The results of the research show that Almuna Bireuen Kindergarten teachers are able to dance the Rateeb Meuseukat Dance and the Islamic character values ​​from the Ratéeb Meuseukat Dance that can be given to students in the learning process at Almuna Kindergarten have been understood so that they are able to foster Islamic character education for students such as aqidah values, worship, morals and muamalah values.